Understanding the transition to work for first degree university graduates in Portugal - Galego, Aurora (2012)
A traditional way of looking at the importance of universities assumes that these are sources of positive effects from the viewpoint of the inputs. In accordance to this perspective, the importance of a university can be measured by its regional/national multiplier effects. This perspective can be complemented with the analysis of the issues associated with the transition to work by their graduates. The paper thus analyses the factors that may be important to explain the time to obtain the first job by first degree students, using a sample of students from one university in Portugal. In doing so, we estimate several specifications of discrete-time duration models. The results show that there are significant differences among the students from the several courses and highlight the importance of the final mark in the course. Nevertheless, in particular, we conclude that there are no significant differences between the area of Economics and Management and the area of Engineering and that these study areas are the most successful ones. We also did not find any significant differences between male and female students. Finally, we also conclude that there are significant differences on the probability of leaving unemployment among the several years considered in the sample, which reflects the business cycle.